Uma análise do nível de proficiência digital de professores do ensino médio de escolas públicas estaduais de Palmas-TO - Correia, Ivete Antunes (Universidade Federal do Tocantins, 2021)
This study aimed to analyze the digital proficiency level of teachers who teach for high school in state public schools in the city of Palmas-TO. Digital Information and Communication Technologies (TDICs), are already present in the teaching-learning processes, and it is of fundamental importance to verify the skills of educators and their real needs, aiming at the appropriate planning of qualifications and training, which result in efficient use of digital tools. Added to this is the possibility of allowing managers who, knowing the reality of teachers, establish effective educational public policies in pursuit of improving teaching. Therefore, this research was based on the application of survey, through the google forms platform, having as a data collection instrument a self-assessment based on the DigCompEdu - Digital Competence Framework for Educators questionnaire, developed by the EU Science Hub. European Commission), validated for the Portuguese population by Dias-Trindade, Moreira and Nunes (2019) and later translated into Brazilian Portuguese by Sales and Santo (2019). The rationale was mainly addressed by studies by Kenski (2007), Carvalho (2018), Dias-Trindade, Moreira and Nunes (2019), besides the Brazilian educational legislation. Contributed to this research 182 teachers who teach in different areas of knowledge in the seven participating schools. Respondents self-reflected on their digital competences in the professional, pedagogical and student-related dimensions, through 21 questions structured in six areas, totaling 84 points. Thus, after the summation, the teacher is classified in one of the six levels of digital proficiency, starting from the beginner level to the innovative level, being the first two levels, A1- Newcomer and A2- Explorer, the beginner; the intermediate levels, B1- Integrator and B2-Specialist; and the most advanced levels, C1- Lider and C2- Pioneer. This research resulted in the overall result that teachers who teach for high school totaled 33 points, being situated at the B1-Integrator level.